Public Knowledge of Diabetes Mellitus: A Cross-Sectional Study - Suaad Abduljabar Abdulwahd Almudhafar (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Diabetes mellitus is a major non-communicable disease with a rapidly increasing global prevalence, making public awareness and understanding essential for disease prevention and management. Specific Background: Assessing public knowledge of diabetes mellitus can provide valuable information for identifying strengths and deficiencies in community awareness regarding the disease. Knowledge Gap: Although diabetes knowledge has been investigated in several populations, limited evidence was available regarding the level of public knowledge in Basrah City, Iraq, particularly concerning specific aspects of diabetes such as complications and management. Aims: This study aimed to assess public knowledge of diabetes mellitus among adults attending primary health care centers in Basrah City. Methods: A descriptive cross-sectional study was conducted between January and May 2009 among 600 diabetic and non-diabetic adults attending four primary health care centers. Knowledge was assessed using a structured questionnaire covering diabetes definition, risk factors, complications, prevention, control, and management. Results: More than half of the participants (55.5%) demonstrated a good level of diabetes knowledge, 35.2% showed an acceptable level, and 9.3% had poor knowledge. Higher proportions of correct responses were observed for diabetes control (71%) and risk factors (69%), whereas lower proportions were found for complications (56.7%) and management (53%). Novelty: This study provides population-based evidence on public diabetes knowledge in Basrah City and identifies specific knowledge deficiencies related to diabetes complications and management. Implications: The findings indicate generally satisfactory public awareness while highlighting the need for targeted educational interventions focusing on diabetes complications and disease management to strengthen community understanding and support diabetes control efforts. Keywords: Diabetes Mellitus, Public Knowledge, Health Awareness, Primary Health Care, Cross-Sectional Study   Key Findings Highlights More than half of participants demonstrated a high level of understanding regarding the disease. Correct responses were highest for disease control and associated risk factors. Deficiencies were identified in awareness related to complications and treatment management.